Pengembangan Wisata Hutan Mangrove di Kampung Kayu Ara Permai - Elis Pirna; Trio Saputra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Mangrove forests are high-value coastal ecosystems that have the potential to be developed as sustainable ecotourism destinations. This study aims to analyze the development of Mangrove Forest Tourism in Kampung Kayu Ara Permai, Sungai Apit District, Siak Regency based on the three pillars of sustainable tourism of the World Tourism Organization (UNWTO), namely environmental, economic, and socio-cultural sustainability. The method used is a descriptive qualitative approach through literature studies and semi-structured interviews with regional managers. The results of the study show that this area has a good mangrove ecosystem with nine species and an average Tourism Suitability Index (IKW) of 76.89% (Suitable/S2 category). From an economic perspective, eight non-timber forest products (NTFPs) downstream products and community-based homestay models have created an equitable distribution of benefits for residents. The socio-cultural dimension is supported by the authenticity of the coastal Malay tradition that is still preserved. However, the three dimensions face challenges in the form of the absence of protection regulations, the absence of a government fixed budget, and low public participation in management evaluation. This study recommends the issuance of regional regulations, the establishment of tourism BUMDes, and the strengthening of community participation as the foundation for sustainable ecotourism development.